Interdisciplinary Consensus on the Care of Elderly Patients with Hip Fractures Through an Orthogeriatric Approach - Olga M. Lesnyak; Alexander Yu. Kochish; Igor G. Belenkiy; Mikhail V. Belov; Kseniia Yu. Belova; Svetlana A. Bozhkova; Tatiana V. Buylova; Nikolay V. Zagorodniy; Larisa A. Marchenkova; Galina A. Pichugina; Svetlana S. Rodionova; Nadezhda K. Runikhina; et al. (Вестник восстановительной медицины)
INTRODUCTION. The development of an interdisciplinary consensus on the care of elderly and elderly patients with proximal femoral fractures is an urgent problem of modern medicine. The provisions of this Consensus will help to establish effective interaction between physicians of different specialties on the basis of their better understanding, which will contribute to the improvement of specialized medical care, saving lives and reducing disability of elderly patients with hip fractures through.